Exploration, analysis and evaluation of Literature Circles in EFL: A case study of higher intermediate young adults in Vietnam - Shelton-Strong, Scott (2012)
Literature represents a unique source of input in English language learning and has been exploited using a variety of models and methodologies over the years. While individual sustained reading has long been recognised to support L2 learning, recent trends have suggested extensive reading be placed within a framework, which integrates response to the text and interaction with peers, to combine reading with debate, discussion, interpretation and reflection. This study represents a close examination, analysis and evaluation of Literature Circles, which reflect such a model, based on a case study conducted in a private language centre in Vietnam. This investigation aims to seek evidence that opportunities for language learning emerge from within the co-construction of communication fostered by the interaction in learnerled, reader response groups, and are developed through collaboration, interpretation and negotiation of meaning. Classroom recordings of such interaction were analysed, and findings discussed which reflect the belief, based on sociocultural theory, that processes leading to opportunities for language acquisition can be identified as an emergent phenomenon, coconstructed within and interrelated to the support of peers within a social environment. Additional qualitative evidence in the form of learner selfevaluation questionnaires, where performance and experience in LCs were reflected upon, suggests that perceptions of self-efficacy were improved through learner participation, leading to increased motivation and learner autonomy. Literature Circles, creating opportunities for collaborative learning at the interface of language learning and literature, are argued to offer a relevant, pedagogically sound approach to fostering language acquisition in ELT.